2023
DOI: 10.3390/biom13050730
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogens: Free Radical Reactivity and Identification of Trans Isomers Relevant to Biological Membranes

Abstract: Plasmalogens are membrane phospholipids with two fatty acid hydrocarbon chains linked to L-glycerol, one containing a characteristic cis-vinyl ether function and the other one being a polyunsaturated fatty acid (PUFA) residue linked through an acyl function. All double bonds in these structures display the cis geometrical configuration due to desaturase enzymatic activity and they are known to be involved in the peroxidation process, whereas the reactivity through cis-trans double bond isomerization has not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Interestingly, in parallel to the influence of lipid oxidation products in the structure and functions of proteins, oxidative damage to peptides and proteins, particularly concerning cysteine and methionine residues, would cause radical damage to lipids, altering their stucture and functions [ 70 , 71 , 72 , 73 ].…”
Section: Secondary and Late Products Of Lipid Peroxidationmentioning
confidence: 99%
“…Interestingly, in parallel to the influence of lipid oxidation products in the structure and functions of proteins, oxidative damage to peptides and proteins, particularly concerning cysteine and methionine residues, would cause radical damage to lipids, altering their stucture and functions [ 70 , 71 , 72 , 73 ].…”
Section: Secondary and Late Products Of Lipid Peroxidationmentioning
confidence: 99%
“…Briefly, the EDTA blood was centrifuged (4000 rpm for 5 min at 4°C) and the cell fraction was isolated based on the high density of the aged cells [ 46 ] and controlled by the use of a cell counter (Scepter 2.0 with Scepter™ Software Pro, EMD Millipore, Darmstadt, Germany). All the subsequent steps were automated, including cell lysis, isolation of the membrane pellets, phospholipid extraction from pellets using the Bligh and Dyer method [ 47 ], transesterification to FAMEs by treatment with a potassium hydroxide/methyl alcohol solution (0.5 mol/L) for 10 min at room temperature and extraction using n-hexane (2 mL) as described in the previous work [ 48 ]. Finally, the FAMEs were analyzed using capillary column gas chromatography on the Agilent 6850 Network GC System (Agilent, USA), equipped with a fused silica capillary column Agilent DB23 (60 m × 0.25 mm × 0.25 μm) and a flame ionization detector.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmalogens are characterized by having the following two fatty acids: one unsaturated fatty acid linked to the glycerol moiety through a cisvinyl ether function and the other PUFA residue linked through an acyl function. An article in this Special Issue reports on the radical reactivity and identification of TFA [19]. In addition to the reported optimal transesterification procedure, it was demonstrated that the vinyl ether reactivity is similar to the reactivity of the arachidonic moiety that contains four C-C double bonds in cis-trans isomerization by thiyl radicals.…”
Section: Biomarkers Of Lipid Damagementioning
confidence: 99%
“…In addition to the reported optimal transesterification procedure, it was demonstrated that the vinyl ether reactivity is similar to the reactivity of the arachidonic moiety that contains four C-C double bonds in cis-trans isomerization by thiyl radicals. Furthermore, a biomimetic Fenton-like model involving plasmalogen-containing liposomes or RBC ghosts, was used to compare peroxidation and isomerization processes, allowing for a full picture of plasmalogen reactivity under free radical conditions [19]. Trans fatty acids can also be produced endogenously from free radicals and thiols, which makes them valuable biomarkers for free radical activity in the human lipidome [12].…”
Section: Biomarkers Of Lipid Damagementioning
confidence: 99%